The Association of Body Mass Index With the Risk of Pulmonary Hypertension in Adults: A Systematic Review and Meta-Analysis of Observational Studies - Pu, Shoufang; Yin, Lidan; Wen, Bi; He, Juan (Frontiers in Medicine, 2022)
Backgrounds: findings regarding the association of body mass index (BMI) and obesity with pulmonary hypertension are conflicting, and there is no systematic review and meta-analysis to summarize the results. Therefore, the purpose of this systematic review and meta-analysis is to assess this relationship. Methods: To detect the relevant articles, PubMed, Scopus, and Google Scholar were searched until February 2021. Included essays were pooled using a random-effect model. I2 test was applied to assess between-study heterogeneity. Results: Sixteen articles (13 cross-sectional and three cohort studies) were included in the meta-analysis. The meta-analysis of cross-sectional studies indicated that obese persons had an increased risk of pulmonary hypertension than non-obese people (Summary Effect Estimate: 1.59 (95% CI: 1.08, 2.32, I2=93). Furthermore, The summary OR for a one-unit increment in BMI was 1.01 (95%CI: 0.99, 1.03), with high heterogeneity, I2= 73.5 %, P heterogeneity <0.001). Conclusion: when comparing obese and non-obese subjects, there is a positive link between obesity and risk of pulmonary hypertension, but no relationship was seen in linear model analysis. However, further prospective and trial studies are required to confirm these findings.